2011
DOI: 10.1186/1757-2215-4-3
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic-Prostaglandin D2 synthase through PGD2 production is involved in the adult ovarian physiology

Abstract: BackgroundThe prostaglandin D2 (PGD2) pathway is involved in numerous biological processes and while it has been identified as a partner of the embryonic sex determining male cascade, the roles it plays in ovarian function remain largely unknown. PGD2 is secreted by two prostaglandin D synthases (Pgds); the male-specific lipocalin (L)-Pgds and the hematopoietic (H)-Pgds.MethodsTo study the expression of the Pgds in the adult ovary, in situ hybridization were performed. Then, to evaluate the role of H-Pgds prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 62 publications
(79 reference statements)
0
22
0
Order By: Relevance
“…However, our experiments cannot ruled out that a sex specific translational regulation of H‐Pgds could take place during gonadal differentiation. To assess the expression of the H‐Pgds protein, we used an antibody directed against H‐Pgds whose specificity has been verified previously (Farhat et al, 2011) and performed co‐staining with the OCT4 (in male) or MVH (in female) germ cell markers and with the SOX9 Sertoli cell marker. This experiment confirmed that H‐Pgds is expressed in somatic and germ cell lineages of both sexes at E11.5, whereas L‐Pgds starts to be expressed in the male gonad (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our experiments cannot ruled out that a sex specific translational regulation of H‐Pgds could take place during gonadal differentiation. To assess the expression of the H‐Pgds protein, we used an antibody directed against H‐Pgds whose specificity has been verified previously (Farhat et al, 2011) and performed co‐staining with the OCT4 (in male) or MVH (in female) germ cell markers and with the SOX9 Sertoli cell marker. This experiment confirmed that H‐Pgds is expressed in somatic and germ cell lineages of both sexes at E11.5, whereas L‐Pgds starts to be expressed in the male gonad (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Digoxigenin‐labeled riboprobes were synthesized using a digoxigenin RNA labeling kit, following the manufacturer's instructions (Roche Diagnostics) and used for in situ hybridization experiments as described earlier (Moniot et al, 2008, 2009). The specificity of the antisense H‐Pgds RNA probe was verified by hybridization with the control sense H‐Pgds RNA probe that showed no significant signal (Farhat et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…PGD2 is abundantly produced by mast cells and Th2 cells, and among a wide range of other body cells (see ref. in Farhat et al (2011 )). PGD2 elicits its downstream effects by activating DP1 and DP2 receptors with opposing effects on cyclic AMP (cAMP) production, and/or phosphoinositol turnover and intracellular Ca2+ mobilization ( Liang et al, 2005 ).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, a region between 45.4 and 45.5 Mb of BTA10 that contains the prostaglandin D2 (PGD2) receptor gene (PTGDR) was highly associated with AFC in ROMO. PGD2 is a signaling molecule involved in biological processes such as platelet aggregation, broncho-constriction and allergic diseases (Farhat et al, 2011), and it also plays an important role as a chemoattractant to recruit immune cells to the feto-maternal interface during pregnancy (Grabner et al, 2017). PGD2 also participates in the embryonic sex-determining male cascade and it seems to interfere with FSH action within granulosa, modulating the balance of proliferation, differentiation and steroidogenic activity of granulosa cells in humans (Farhat et al, 2011).…”
Section: Discussionmentioning
confidence: 99%